One-year outcomes of elderly acute cholecystitis patients by index treatment - Lluís, Núria; Villodre, Celia; Guilabert, Lucía; de Castro, Isabel; Zapater, Pedro; Martínez, Belén; Aparicio, José R.; Lluís, Fèlix; de-Madaria, Enrique (Frontiers in Surgery, 2025)
BackgroundStrategies for managing the elderly with acute cholecystitis need to be refined.AimsTo examine additional procedures, hospital readmissions, and outpatient visits in the year following the index admission.Patients and methodsSingle-institution retrospective study of fifty consecutive patients aged ≥70 years admitted with acute cholecystitis. A propensity score matching analysis adjusted for demographic and clinical variables was carried out.ResultsThe one-year rates of additional procedures were 0%, 47.4%, and 72.7% for surgery, supportive care (SC), and percutaneous gallbladder drainage (PCGD), respectively. The one-year readmission rate was 0%, 15.8%, and 50% after these index procedures, respectively. After propensity score analysis, patients who received SC (55.6% vs. 0%, P = .03) or PCGD (77.8% vs. 0%, P = .002) had a higher rate of additional procedures compared to those who underwent surgery. Additionally, patients receiving PCGD had a higher readmission rate than those undergoing surgery (55.6% vs. 0%, P = .03). Nine patients who received SC and nine patients who received PCGD could have potentially undergone surgery during the index admission. This would have resulted in improved one-year outcomes.ConclusionCholecystectomy during the index hospitalization may provide better one-year outcomes than SC or PCGD in at least 50% of patients ≥70 years with acute cholecystitis.